Analysis of Consumer Buying Interest in Sanitary Napkin Products that are Green Products - Jannah, Nur; Sarie, Rena Febrita; Hariyanto, Krisnadhi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
Environmentally friendly products are designed and produced without causing adverse environmental impacts, including the use of sustainable materials. This is particularly important for sanitary napkin products, which serve as vital support for women during menstruation. For Generation Z women, sanitary napkins are not only viewed as protective products but also as a reflection of environmental values that enhance self-confidence in social interactions. This study aims to examine the factors influencing Generation Z’s purchase intention of green sanitary napkin products, focusing on the role of environmental values (environmental awareness, consumption value, and eco-label). This quantitative research employed a purposive sampling technique involving 100 female respondents from Generation Z in Malang who have experience using eco-friendly sanitary napkin products. The measurement of research variables was conducted using validated and reliable instruments, with reliability confirmed by Cronbach’s Alpha and Composite Reliability (CR) tests, and validity tested through convergent and discriminant validity. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method following the stages of model measurement (outer model), structural model (inner model), and hypothesis testing. The results show that eco-labels do not significantly influence purchase intention, while environmental awareness and consumption value have a significant effect. This indicates that although Generation Z in Malang is aware of the importance of environmental protection, eco-labels are not the main factor in their purchasing decisions. Instead, their understanding of the value and benefits of environmentally friendly products plays a more dominant role.